Експлуатаційні характеристики стрілецького озброєння при використанні боєприпасів довготривалого зберігання - Бірюков, І. Ю.; Баулін, Дмитро Станіславович (НТУ "ХПІ", 2008)
In article is considered influence of periods storage ammunitions on operational characteristics of small arms. Are offered the model of operation ammunitions at various stages of storage and practical recommendations on their further use.
Keywords: стрілецька зброя; порох; балістичні властивості; стійкість порохів; експлуатація боєприпасів